Diagnosis and analysis of environmental degradation: a case study of the Bodocongó reservoir (Research, Society and Development, 2021)
The environmental degradation of urban watersheds has brought great damage to its drainage network and, consequently, to the entire society around it. Ineffective management, associated with the lack of public policies, with regard to inspection and basic sanitation, ends up promoting the inadequate disposal of sewage and garbage in water bodies present in urban areas. Anthropogenic actions on the perimeter of the Bodocongó reservoir cause negative impacts such as water and soil contamination and erosion processes. The population increase around the dam, the creation of a public park, housing condominiums and the lack of inspection, brought great impacts on the water body basin. The constant input of domestic and industrial effluents left the source hypereutrophic, with high levels of total coliforms. Educational actions and public policies aimed at recovering the historically important source for the city of Campina Grande are necessary.